Assessing Work-Life Balance And Teaching Outcomes In Self-Financing Colleges In Kerala - Salim, Naisa; Thavamalar, Dr. D H (Metallurgical and Materials Engineering, 2025)
The study investigates work-life balance as a predictor of teaching performance among self-financing college teachers in Ernakulam district, Kerala. As private higher education institutions are growing at a rapid pace, teachers experience job insecurity, overwork, and lack of institutional support, impeding their well-being and academic performance. With a descriptive-analytic approach supported by Work-Life Border Theory and the Job Demands-Resources Model, the responses of 91 teachers were compared quantitatively using descriptive and inferential statistics. The findings report a young, female-dominated workforce balancing professional and heavy caregiving responsibilities, often confronted with role overload, stress, and moderate institutional support. Quality of Work Life (QWL) dimensions—i.e., work quality, work-life balance, stress management, and financial management—were significantly connected to personality development and career progression but less connected to teaching and research skills. Regression analysis identified these dimensions as predictors of teacher development outcomes, reflecting the importance of supportive work culture in enhancing career progression and personal well-being. The study highlights the ongoing negotiation between professional and personal requirements that the faculty are in, with many experiencing conflicts that intrude into personal time, as envisaged in Life Border Theory. With some flexibility in institutions, wellness programs are still insufficient to completely negate worklife tensions. Gender, household responsibilities, and educational levels had significant roles in predicting the outcomes of QWL, with female faculty and those having organized home roles having more work-life congruence. The research highlights the need for selected institutional policies to enhance the working conditions of faculty members, offer better opportunities for professional development, and facilitate well-being to ultimately enhance teaching performance and professional development in Kerala’s self-financing college system.